Acute effect of kinesiotaping on technical skills of wheelchair basketball players - Cimen, K.; Sanal, A.; Özen, G.; Atar, Ö.; Ünsalan, M. (International Journal of Disabilities Sports and Health Sciences, 2023)
The purpose of this research kinesiology taping (KT) is to increase the blood and lymph circulation under the skin and provide the athlete with a comfortable movement capacity. For this purpose, we aim to examine the effect of KT on the shoulder and supraspinatus muscles of wheelchair basketball players on the technical skills of athletes. Ten male wheelchair basketball players between the ages of 20 and 40 participated in the study. In the study, kinesiology tape was applied to the shoulder and supraspinatus muscle regions of the athletes. To evaluate the effect of KT regional shooting (2p), tourniquet, slalom, and sprint tests were applied before and after taping. SPSS 25 statistical program was used for the analysis of the data. The significance value for the analysis was accepted as 0.05. According to the research findings, it was determined that KT was effective in the 2nd, 3rd, and 4th regions in shooting from 5 regions, and KT was also effective in 20m sprint, right tourniquet throw, and slalom skills with and without the ball (p<0.05). We can say that KT affects shots made from positions that see the basket from the opposite and diagonal, increasing the dribbling skill and sprint performance. During the competition, it is recommended that the athletes do it on the shoulder and supraspinatus muscle areas.